Pengaruh Profitabilitas dan Corporate Governance Terhadap Tax Avoidance Pada Perusahaan BUMN Yang Terdaftar Di Bursa Efek Indonesia Periode 2014-2018 - Saeful Fachri; Indra Sulistiana; Muhammad Saefi Mubarok (ITB AAS INDONESIA, 2021)
Tax collection in Indonesia is still experiencing many obstacles, as a result, the effectiveness of tax collection has continued to decline from 2012 to 2015 with an average of 3.74%. This study has the aim of knowing the factors that influence Tax Avoidance. The research method used is descriptive method with a quantitative approach. The t-test results show that the profitability variable has a significant level of 0.414 greater than 0.05 with a t-statistic of -0.882 and a t-table of 1.992, which means the t-count is smaller than the t-table. Furthermore, the results show that the independent commissioner variable has a t-count value that is smaller than the t-table value (-3.211